A proposed clinical criteria to determine the type of surgical management for Resistant or Relapsed Clubfeet (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To introduce a simple clinical criteria for assessment of residual or relapsed idiopathic club foot and to improve its outcome by appropriate surgical management.Methods: This descriptive study was conducted in the Department of Pediatric Orthopedic surgeryThe Children’s Hospital, Lahore, from June 2014 to June 2018.All patients meeting the inclusion criteria were clinically assessed for dorsolateral hump, midfoot crease, hind foot crease and equinus and were divided into three groups according to the severity and number of these deformities present. Surgery was done according to the pre- decided plan for each group on all club feet. Patients were followed up at 3 months, 6 months and at 1 year after surgery and outcome were evaluated according to the functional rating system for club foot surgery.Results: We had a total of 35 children with mean age of 21 months (range 6 to 36 months). Male were 24(68.5%) and female were 11(31.4%). Bilateral clubfeet were present in 15(42.8%) and unilateral residual idiopathic club foot in 20(57.1%) making it 50 club feet. A total of 8 (16%) patients had flexible dorsolateral hump only so required posteromedial release procedure while 23 (46%) patients had flexible dorsolateral hump with half midfoot crease with or without hind foot equinus so required posteromedial and abductor planter release. In 19 (38%) feet rigid dorsolateral hump with or without other deformities were present and they underwent posteromedial, lateral and abductor planter release. Outcome was excellent in 26 (52%), good in 19 (38%), fair in 4 (8%) and poor in 1 (2%) of patients.Conclusion: The choice of surgical procedure according to the properly assessed residual or relapsed deformity by our proposed clinical criteria makes the surgical management precise and gives excellent and good results in residual or relapsed idiopathic club foot.